Depression, anxiety and stress during the COVID-19 pandemic in dental students - Nohelia Pérez-Bejarano; José Miguel Gamarra-Insfrán; Clarisse Virginia Díaz-Reissner; Carlos G. Adorno; Vicente Reinaldo Fretes-López; Rebecca Carmina Diaz-Carbajal; Víctor R. Adorno (Universidad de Antioquia, 2022)
Introduction: in December 2019, a case of pneumonia caused by coronavirus 2 (SARS-CoV-2) was reported in the world. Currently, Paraguay has registered more than 428,000 confirmed cases and more than 13,500 deaths. In this context, teaching has had to be transferred to the virtual environment, generating reactive behavioral modifications at all levels arising from various causes: difficulty in accessing computer elements, the need in varying degrees of relearning in an unusual environment and, above all, uncertainty. The aim of this study was to determine the levels of depression, anxiety and stress during the covid-19 pandemic in dental students. Methods: for this cross-sectional descriptive observational study, undergraduate students from the School of Dentistry of the National University of Asunción, enrolled in the academic period 2021, were included. The Depression, Anxiety and Stress (DASS-21) short form scale was used. Each of the three axes (depression, anxiety, and stress) contains 7 items, divided into subscales of similar content. The scores were categorized into five ordered groups (normal, mild, moderate, severe, and very severe). Results: dentistry students presented symptoms of depression and anxiety with symptoms of moderate anxiety in 42.58%; 1.29% presented severe depression. Conclusion: most of the dental students presented depression and anxiety with very common symptoms such as the inability to relax, lack of initiative, irritability and nervousness.